Evaluation of two‐step haemoglobin screening with HemoCue for blood donor qualification in mobile collection sites. Issue 4 (11th June 2014) - Gómez‐Simón, A.; Plaza, E. M.; Torregrosa, J. M.; Ferrer‐Marín, F.; Sánchez‐Guiu, I.; Vicente, V.; Lozano, M. L.; Rivera, J.
<x xml:space="preserve">Abstract</x> Background and Objectives Inaccuracy of fingerstick haemoglobin compromises donor's health and losses blood donations. We evaluated the benefit of double haemoglobin screening with HemoCue. Study Design and Methods Blood donors underwent fingerstick screening by HemoCue and were driven for donation if capillary haemoglobin was within the regulatory range. Those failing were drawn venous blood and donated if their venous haemoglobin determined with HemoCue was acceptable. Results Of 276 605 donor clinic visits, 10 011 (3·6%) were assessed by two‐step haemoglobin screening using HemoCue, because of low (n = 9444) or high (n = 567) capillary haemoglobin. Among these, 2561 (25·6%) were deemed eligible [recovered donations]. The recovery rate was 23·8% and 55·0% among donors presenting with low and high capillary haemoglobin, respectively. In both categories of attempted donations, capillary and venous haemoglobin with HemoCue correlated significantly in recovered donors (R2 ≈ 0·5–0·7) but not in deferred visits (R2 < 0·15). Venous haemoglobin with HemoCue and by haematological analyzer significantly correlated in all donations attempts (R2 ≈ 0·7). Donors presenting with low capillary haemoglobin showed small bias between capillary and venous haemoglobin by HemoCue (−2·4 ± 6·2 g/l), fingerstick haemoglobin and venous haemoglobin with counter (1·3 ± 7·3 g/l), and venous haemoglobin with HemoCue and counter (3·7 ± 3·9 g/l). This bias was slightly greater in donors with high capillary haemoglobin (−7·5 ± 7·8, 13·7 ± 7·5, and 6·2 ± 7·5, respectively). Double haemoglobin screening by HemoCue reached an accuracy of 87·3% for qualifying donors presenting with low fingerstick haemoglobin. Conclusions Double haemoglobin measurement with HemoCue [fingerstick and venous blood if required] is feasible and allows a significant recovery of blood donations.